Race and Socioeconomic Status: Interlinked Drivers of Sleep Health Disparities (Mary Ann Liebert, 2023)
The effect of race and socioeconomic status on sleep disorders has significant effects on the availability of healthcare and health outcomes. This paper examines how race and SES contribute to sleep health disparities, emphasizing the importance of understanding their impact on sleep disorders and treatment particularly in minority populations and veterans.